Prospects of Using Service Oriented Architecture in Interorganizational Integration - Polak, Przemysław (Advanced Information Technologies for Management – AITM 2008, 2008)
Service oriented architecture (SOA) is usually considered to be a method of integrating IT systems within an organization and stress is placed on advantages resulting form faster and cheaper adopting of applications to the business needs of an organization. Instead, the article presents the discussion of prospects of using SOA in the integration of IT systems of separate organizations. The author argues that implementing SOA in the interorganizational integration would create a new model of integration which can be named interorganizational services bus, and integrating both internal and external systems using the same architectural approach can generate large savings in information systems management.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 35, s. 150-157